Factors affecting alcohol consumption: The case of Penang, Malaysia - Cheah, Yong Kang (Penerbit UKM (UKM Press), 2014)
In light of the increases in alcohol-induced diseases and social problems, the present study sets out to examine the factors affecting alcohol consumption among adults in Penang (Malaysia) using a cross-sectional survey sample consisting of 398 respondents.The results of the logistic regression analysis show that age, gender, ethnicity, marital status and smoking are significantly associated with alcohol consumption. In particular, males (OR: 3.720; 95% CI: 1.939, 7.136), Chinese (OR: 3.628; 95% CI: 1.808, 7.279) and smokers (OR: 5.083; 95% CI: 1.876, 13.774) are more likely to consume alcohol than others, whereas, old individuals (OR: 0.971; 95% CI: 0.941, 1.002), Malays (OR: 0.059; 95% CI: 0.021, 0.165) and married individuals (OR: 0.419; 95% CI: 0.211, 0.833) are less likely to consume alcohol than others.Based on the findings of the present study, several intervention strategies toward reducing alcohol consumption are proposed. Specifically, these strategies should be targeted at young individuals, males, Chinese, unmarried individuals and smokers.